Serum nitric oxide, catalase, superoxide dismutase, and malondialdehyde status in patients with ankylosing spondylitis - Ozgocmen, S; Sogut, S; Ardicoglu, O; Fadillioglu, E; Pekkutucu, I; Akyol, O (Springer Heidelberg, 2004)
In this study, serum antioxidant and oxygen derived free radical status of patients with ankylosing spondylitis (AS) was investigated and compared with that of age- and sex-matched healthy controls. The relationship of these parameters to disease activity indices was also examined. Thirty patients with AS not currently under disease-modifying antirheumatic drug (DMARD) treatment (e.g., sulfasalazine or methotrexate) (15 active and 15 inactive) and 16 age- and sex-matched healthy controls were included in the study. Catalase (EC 1.11.1.6), total (Cu-Zn and Mn) superoxide dismutase (SOD) (EC 1.15.1.1) activities, and malondialdehyde (MDA), nitrite (NO2-), and nitrate (NO3-) levels as indices of nitric oxide (NO) production were evaluated using appropriate methods. There was no statistically significant difference found in SOD activity or NO and MDA levels between active and inactive patients. Inactive patients showed no significant difference in all the measured oxidant/antioxidant parameters when compared to healthy controls. Active patients had significantly higher levels of MDA and catalase enzyme activity (P=0.002 and P=0.007, respectively). There was no significant correlation between oxidant/antioxidant parameters and disease activity, C-reactive protein, erythrocyte sedimentation rate, or Bath Ankylosing Spondylitis Disease Activity Index (CRP, ESR, or BASDAI) in either group, except catalase enzyme activity, which had a significant correlation with CRP and ESR levels in active patients (r=0.69 and P=0.004, r=0.52 and P=0.04, respectively). Our results indicate that oxidative stress and lipid peroxidation are accelerated in untreated patients with active AS. Serum catalase activity may be closely related to disease activity. In this regard, we underscore the likely benefit of some therapeutic interventions including high-potential antioxidants that will potentiate the antioxidant defense mechanism and reduce peroxidation in the management of AS.
Keywords: ankylosing spondylitis; catalase; malondialdehyde; nitric oxide; superoxide dismutase; xanthine oxidase